A methodology for the diagnosis and follow-up of the evolution of acute hepatitis in childhood. The Working Group of the Section of Pediatric Gastroenterology and Nutrition of the Portuguese Pediatrics Society. - Dias, J A (1995)
The Working Group of the Section of Paediatric Gastroenterology and Nutrition of the Portuguese Society of Paediatrics established a protocol for the investigation of children with acute hepatitis. The main purpose of this proposal is to allow appropriate etiologic investigations and avoid unnecessary tests that are expensive and do not add relevant information for the correct follow-up of these patients.